FORMATION OF REGIONAL ENDOWMENT FUNDS ACCORDING TO LAW NUMBER 1 OF 2022 CONCERNING FINANCIAL RELATIONS BETWEEN THE CENTRAL GOVERNMENT AND REGIONAL GOVERNMENTS - Ridho, Muhammad; NAM Sihombing, Eka; Afnila, Afnila (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
The government continues to refine and strengthen the policy of governance of financial relations between the central and regional governments in order to achieve national goals by enacting Law Number 1 of 2022 concerning Financial Relations between the Central and Regional Governments, which regulates regional endowment funds. This regulation provides space for the formation of Regional Endowment Funds but also provides limitations with certain criteria. Law Number 1 of 2022 stipulates that the formation must consider, among other things, regional fiscal capacity and the fulfillment of mandatory Government Affairs needs related to basic public services. The objectives of this research areTo determine the urgency of establishing a Regional Endowment Fund.The results of the study show: First, the factors that encourage the formation of DAD, namely 1) The formation of DAD becomes a strategy to ensure the sustainability of long-term and cross-generational regional finances; 2) Optimization of regional spending in regions with established fiscal policies; 3) Encouraging regional investment activities in an effort to increase regional income. Second, the governance scheme in the formation of DAD is the establishment, management, use, and supervision. All of these stages must receive support from all parties, especially regional leaders.